Reconstruction of the orbital floor with polydioxanone: a long-term clinical survey of up to 12 years. Issue 8 (October 2015) - Beck-Broichsitter, Benedicta Elisabeth; Acar, Carolin; Kandzia, Christian; Jochens, Arne; Wiltfang, Jörg; Becker, Stephan T.
Abstract: Fractures of the orbital floor are common in injured patients, who often require operation to prevent complications and, among other materials, polydioxanone is widely used. The aim of this study was to evaluate the long-term outcomes of fractures of the orbital floor that had been reconstructed with polydioxanone foil. A total of 101 patients (73 men and 28 women) who had reconstruction of the orbital floor for defects of 2 cm 2 or smaller with polydioxanone implants, over a mean (SD) time period of 8 (2) years were evaluated. Sensitivity of the infraorbital nerve, ocular motility, and diplopia were evaluated and correlated with perioperative values. Persistent hyperaesthesia was found in 15 patients, whereas in another 15 the hyperaesthesia recovered completely over time. Three patients had double vision during follow-up. Twenty patients with preoperative diplopia had no persistent double vision postoperatively, and 15 patients with disturbed ocular motility recovered completely. Two patients had persistently disturbed motility, and one patient had enophthalmos. There was a significant association between hyperaesthesia preoperatively and postoperatively (p= 0.005). In most patients reconstruction of the orbital floor with polydioxanone was successful. Long-term complications such as diplopia, compromised bulbar motility, and hyperaesthesia of the cheek were seen in a few cases, but might not have been solely related to the use of polydioxanone.